Pengaruh Model Pembelajaran (Team Assisted Individually dan Think Paire Share) Dan Gaya Kognitif Terhadap Hasil Belajar Kimia Siswa Kelas X IPA Pada Materi Larutan Elektrolit Redoks - Ita Roslita (Universitas Mathla'ul Anwar Banten, 2017)
This research is aimed to investiagate: (1) the effect of Team Assisted Individually (TAI) and Think Pair Share (TPS) Learning Models towards learning results. (2) the difference of learning results at Field Independent (FI) and Field dependent (FD) students. (3) The interaction effect of learning model and cognitive style towards learning result. (4) The effect of Team Assisted Individually (TAI) and Think Pair Share (TPS) Learning Models towards learning results of field independent student. (5) The effect of Team Assisted Individually (TAI) and Think Pair Share (TPS) Learning Models towards learning results of field dependent student. Method used in this research is experimental method with factorial 2 x 2 research design. The result of hypothesis analysis shows that (1) the student’s learning result of Team Assisted Individually (TAI) class is higher than Think Pair Share (TPS) class. (2) the learning result of field independent student is higher than field dependent student. (3) there is interaction between learning models and cognitive style towards learning results. (4) the learning results of field independent student at Team Assisted Individually (TAI) class is higher than Think Pair Share (TPS) class. (5) the learning results of field dependent student at Team Assisted Individually (TAI) class is higher than Think Pair Share (TPS) class.